PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA KONSEP SUHU DAN KALOR - Ahmad Farisi; Abdul Hamid; Melvina Melvina (FKIP Unsyiah, 2017)
This study aims to see the effect of learning model Problem Based Learning (PBL) on students critical thinking skills on the concept of temperature and heat in SMP Negeri 1 kaway XVI. The approach used is a quantitative approach in the form of experimental research. The sampling technique is using class of purposive sampling, the selected sample is class VII-1 (22 students) as experiment class, with learning model used PBL model and class VII-2 (20 students) as control class, with the model of learning used by Direct Instruction model. The data collected based on the results of the pre-test and post-test are based on the indicators of critical thinking, namely: (1) provide a simple explanation; (2) to conclude, and; (3) provide further explanation. Then the data is analyzed using t-test. Hypothesis test used by 1 side test is right side, with criterion accept Ha if t-count t-table and Ha rejected if t-count t-table. Hypothesis test results obtained tcount = 6.71 and ttable = 1.68, it can be concluded t-count t-table, in other words Ha accepted. The conclusion of this research is the effect of using Problem Based Learning (PBL) model on students' critical thinking ability on concept of temperature and heat in SMP Negeri 1 Kaway XVI. Based on the above conclusions the authors suggest to use the PBL learning model in teaching physics lessons.